PENGARUH FAKTOR-FAKTOR KINERJA PEGAWAI DAN KEPUASAN KERJA (Studi Pada Kantor Dinas Koperasi Dan UMKM Kabupaten Wonosobo) - Endah Winarti HS; Ida Martini Alriani; Sodikin Manaf (JURNAL EKONOMI MANAJEMEN AKUNTANSI, 2013)
This research purpose to analyze job satisfaction and influence factor (the study in the Office Dinas Koperasi and UMKM Kabupaten Wonosobo). The population in this research was all the official Dinas Koperasi and UMKM Kabupaten Wonosobo that were numbering 30 people. The sample that in took was all the population in made the sample that is using the method of the census research. Analytical method applied is content  validity and reliability, goodness of fit model, analysis regression model or Moderated Regression Analysis (MRA).Result of hypothesis testing showed that the value t count towards the work motivation  to employee performance 3,026 > t table = 1,708 with the significant of 0,003 < α = 0,05 (significant). Thereby hypothesis 1 (H1) that affect the work motivation to employee performance in the  Dinas Koperasi and UMKM Kabupaten Wonosobo proven. Hypothesis (H2) t values affect individual competence variables to the table an employee performance  2,940 > t table = 1,708 and the number of significance = 0,004 < α = 0,05 (significant) is proven. Hypothesis (H3) that work environment proven moderated influence work motivation towards empyoyee performance 2,799 > t tablel 1,708 and the number of significance = 0,009 < a = 0,05 (signifikan) is proven. Hypothesis (H4) that work environment proven moderated influence individual competence  towards employee performance 2,608 > t tablel 1,708 and the number of significance = 0,012 < a = 0,05 (signifikan) is proven. Produced by the value t counted from the influence of the employee performance of the variable on job satisfaction of 2,460 > t the table = 1,701 and the significant figure = 0,020 < α = 0,05 (significant), therefore then the hypothesis 5 (H5) that is proven.Keyword : Work motivation, individual competence, work environment, employee performance and job satisfaction.